Endogenous insensitivity to the Orco agonist VUAA1 reveals novel olfactory receptor complex properties in the specialist fly Mayetiola destructor - Jacob A. Corcoran (Nature Portfolio, 2018)
Abstract Insect olfactory receptors are routinely expressed in heterologous systems for functional characterisation. It was recently discovered that the essential olfactory receptor co-receptor (Orco) of the Hessian fly, Mayetiola destructor (Mdes), does not respond to the agonist VUAA1, which activates Orco in all other insects analysed to date. Here, using a mutagenesis-based approach we identified three residues in MdesOrco, located in different transmembrane helices as supported by 3D modelling, that confer sensitivity to VUAA1. Reciprocal mutations in Drosophila melanogaster (Dmel) and the noctuid moth Agrotis segetum (Aseg) Orcos diminish sensitivity of these proteins to VUAA1. Additionally, mutating these residues in DmelOrco and AsegOrco compromised odourant receptor (OR) dependent ligand-induced Orco activation. In contrast, both wild-type and VUAA1-sensitive MdesOrco were capable of forming functional receptor complexes when coupled to ORs from all three species, suggesting unique complex properties in M. destructor, and that not all olfactory receptor complexes are “created” equal.